Understanding the Light‐Intensity Dependence of the Short‐Circuit Current of Organic Solar Cells. Issue 10 (18th August 2020) - Hartnagel, Paula; Kirchartz, Thomas
Abstract: In organic solar cells, bimolecular recombination is a key factor limiting the device performance and creating the need for characterization. Light‐intensity‐dependent short‐circuit current density measurements are a frequently used tool to qualitatively analyze bimolecular recombination in a device. When applying a 0D model, bimolecular recombination is expected to reduce the otherwise linear correlation of the short‐circuit current density J sc and the light intensity Φ to a sublinear trend. It is shown by numerical simulations that the slope of the J sc –Φ curve is affected by the recombination mechanism (direct or via traps), the spatial distribution of charge carriers and—in thick solar cells—by space charge effects. Only the combination of these effects allows proper explanation of the different cases, some of which cannot be explained in a simple 0D device model. Abstract : The light‐intensity dependence of the short‐circuit current is a frequently used assay of bimolecular recombination. The influence of direct and trap‐assisted recombination on the measurements for different absorber thicknesses is explored using numerical simulations. They reveal the impact of spatially resolved charge‐carrier densities and space charges suggesting new approaches to interpreting light‐intensity‐dependent short‐circuit current measurements.